2010
DOI: 10.1016/j.jcrs.2009.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of measurements with a double-pass system

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
129
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(150 citation statements)
references
References 12 publications
15
129
2
4
Order By: Relevance
“…Tarrasa, Spain), an optical instrument based on the double-pass technique widely validated [27][28][29]. This device provides information on higher-order aberrations, diffraction, and scattered light, using an infrared laser diode (λ = 780nm) as light source.…”
Section: Retinal-image Quality: Strehl Ratio and Mtf Cutoffmentioning
confidence: 99%
See 2 more Smart Citations
“…Tarrasa, Spain), an optical instrument based on the double-pass technique widely validated [27][28][29]. This device provides information on higher-order aberrations, diffraction, and scattered light, using an infrared laser diode (λ = 780nm) as light source.…”
Section: Retinal-image Quality: Strehl Ratio and Mtf Cutoffmentioning
confidence: 99%
“…A lower value indicates lower retinalimage quality due to a greater influence of ocular aberrations and scattered light. On the other hand, the MTF represents the loss of contrast produced by the eye's optics on a sinusoidal grating as a function of its spatial frequency [29]. The MTF cutoff theoretically represents the spatial frequency, in cycles per degree (cpd), corresponding to an MTF value of 0.…”
Section: Retinal-image Quality: Strehl Ratio and Mtf Cutoffmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 13 shows the double-pass images and the corresponding intensity profiles as a function of the angle (averaged section of the double-pass image), MTFs, and simulated vision using a standard visual acuity chart for an emmetropic eye, an eye with uncorrected astigmatism and an eye with spherical ametropia. The measurements were taken with the Optical Quality Analysis System (OQAS, Visiometrics, S.L., Spain) (Güell et al, 2006;Saad et al, 2010;Vilaseca et al, 2010a), which is a double-pass system currently available for use in daily clinical practice that includes this application. The double-pass technique has been used extensively to determine the optical quality of the eye, mainly by means of the ocular MTF.…”
Section: Clinical Assessment Of Retinal Image Quality In Eyes With Asmentioning
confidence: 99%
“…From this technique an objective scattering index (OSI) proposed by Artal et al (15) can be computed. This parameter takes into account the forward-scattered light and has been validated in several studies (16) (17) (18). Other studies have suggested the usefulness of this parameter in the clinical prediction of intraocular scattering (16) (19) (20) and it has been shown to be useful for grading nuclear, cortical and posterior subcapsular cataracts (15)(21).…”
Section: Introductionmentioning
confidence: 97%